Dekonstruksi Identitas Komunitas Punk (Studi Kasus Komunitas Taring Babi di Kelurahan Lenteng Agung, Kecamatan Jagakarsa, Jakarta Selatan) - Enjanis feronika suhardi (HK-Publishing, 2022)
Abstract:The punk community is part of a social phenomenon that occurs and continues to grow in people's lives. Punk was born to convey a form of voice through criticism and apply a resistance of its own in various ways. Punk is often regarded as a disturbing party, disturbing the comfort and order of the living order of society to the assumption that punk is a threat. Negative stigma continues to be attached to the punk community such as shabby clothing styles, parties who commit crimes, as thugs, troublemakers and even drug users. In order to change the negative views circulating in the community, the Taring Babi punk community is here to become a punk community that has a different basis for thinking about punk life today. The presence of the Taring Babi community aims to rebuild a positive identity and make various efforts to erode and even eliminate the negative views of the community. Research on the deconstruction of the social identity of punk children in the Taring Babi community study in Lenteng Agung Village, Jagakarsa District, South Jakarta would like to discuss how the process of social identity formation is felt and carried out by the Taring Babi community which includes various efforts to rebuild a positive identity. The method used in this research is descriptive qualitative. The data obtained came from observations, interviews, documentation, and literature study.Keywords: Deconstruction, Social Identity, Punk